Species conservation profile of the rare and endemic trapdoor spider Calathotarsus simoni (Araneae, Migidae) from Central Argentina - Ferretti, Nelson Edgardo (2017)
Background: Calathotarsus simoni Schiapelli & Gerschman 1975 is the only species of Migidae in Argentina. It is a rare and endemic spider only found in relict grassland of mountain systems in the province of Buenos Aires. This species is a habitat specialist spider occupying specific areas with certain microclimatic conditions on hilly and rocky grassland areas at about 500-1500 meters above sea level. New information: The observed extent of occurrence (EOO) is 7207 km2 and the area of occupancy (AOO) is 16 km2. Two locations are identified based on the threat event related to the invasion of the species habitat by alien woody plants. In addition, intensive cattle production and agriculture also constitute relevant threats to the species.